How education background affects design outcome: teaching product development to mechanical engineers, industrial designers and managers - Silva, A.; Leite, M.; Vilas-Boas, J.; Simões, R. (European Journal of Engineering Education, 2019)
Product design and development (PDD) is a current topic of academic and industrial research. Emphasis on innovation and entrepreneurship, as well as design thinking and creativity has been recently pulled together into the teaching and research on PDD. This paper looks into a multidisciplinary setting made up of three similar but independent PDD masters courses taught at three higher education institutions, having the same assessment, syllabus, assignments and outcomes. As expected, students’ projects foci are different. The outcomes of this experience were confronted with an ex-post literature review, which generated thorough guidelines that supported an innovative proposal for PDD education, to be implemented into an interdisciplinary Summer School. Significant generalisable contributions for educating modern engineers, designers and business entrepreneurs are expected, instead of just teaching methods of engineering, design and entrepreneurship at the case universities. The limitation of the used inductive reasoning concerns ‘truth’ being suggested but not assured.